Extranodal Extension on Sentinel Lymph Node Dissection: Why should we Treat it Differently?. Issue 10 (October 2014) - Choi, Audrey H.; Surrusco, Matthew; Rodriguez, Samuel; Bahjri, Khaled; Solomon, Naveen; Garberoglio, Carlos; Lum, Sharon; Senthil, Maheswari
American College of Surgeons Oncology Group Z0011 concluded that axillary lymph node dissection (ALND) may be avoided in selected patients with breast cancer with limited axillary nodal metastasis on sentinel lymph node dissection (SLND). However, patients with extranodal extension (ENE) were excluded to the follow existing standard of care, which is completion ALND. The significance of ENE detected on SLND is not well defined. Our objective was to determine the impact of ENE found on SLND on nonsentinel lymph node (NSLN) metastasis, recurrence, and overall mortality. We evaluated patients with breast cancer treated at a tertiary cancer center from 2005 to 2012. SLND was performed in 655 patients. Of those, 478 of 655 (73.0%) patients had no SLN metastases, 124 of 655 (18.9%) had SLN metastases without ENE (SLN-ENE), and 53 of 655 (8.1%) had SLN metastases with ENE (SLN1ENE). Of patients undergoing ALND, NSLN metastasis was detected in 37 of 84 (44.0%) of patients in the SLN-ENE group and 26 of 45 (57.8%) patients in the SLN1ENE group ( P = 0.14). On adjusted analyses, ENE was associated with increased disease recurrence (odds ratio [OR], 5.48; 95% confidence interval [CI], 1.23 to 24.48; P = 0.03) as well as increased overall mortality (OR, 8.16; 95% CI, 1.72 to 38.63; P = 0.01). In conclusion, ENE is associated with increased overall axillary nodal burden, disease recurrence, and overall mortality.